Multi-channel photodissociation and XUV-induced charge transfer dynamics in strong-field-ionized methyl iodide studied with time-resolved recoil-frame covariance imaging - Allum Felix; Anders Nils; Brouard Mark; Bucksbaum Phil H; Burt Michael; Downes-Ward Briony; Grundmann Sven; Harries James; Ishimura Yudai; Iwayama Hiroshi; Kaiser Leon; Kukk Edwin; et al. (Royal Society of Chemistry, 2025)
The photodissociation dynamics of strong-field ionized methyl iodide (CH3I) were probed using intense extreme ultraviolet (XUV) radiation produced by the SPring-8 Angstrom Compact free electron LAser (SACLA). Strong-field ionization and subsequent fragmentation of CH3I was initiated by an intense femtosecond infrared (IR) pulse. The ensuing fragmentation and charge transfer processes following multiple ionization by the XUV pulse at a range of pump–probe delays were followed in a multi-mass ion velocity-map imaging (VMI) experiment. Simultaneous imaging of a wide range of resultant ions allowed for additional insight into the complex dynamics by elucidating correlations between the momenta of different fragment ions using time-resolved recoil-frame covariance imaging analysis. The comprehensive picture of the photodynamics that can be extracted provides promising evidence that the techniques described here could be applied to study ultrafast photochemistry in a range of molecular systems at high count rates using state-of-the-art advanced light sources.